2018
DOI: 10.2507/29th.daaam.proceedings.136
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Materials Used in 3D-Printing Technology with Different Analysis Techniques

Abstract: 3D inkjet printing is mainly a powder-based method where layers of solid particles are bounded together by means of a printed liquid material to generate a 3D model. In this process, it is necessary to control different parameters that can significantly affect the quality of 3D printed parts, such as: chemical composition, structural elucidation, particles morphology, among others. For this reason, the purpose of this research was to develop a study of the chemical and physical properties of the two involved m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The band evolution in Region 2 ( Figure 6 b,d) is more complicated to describe because these peaks are very weak in the infrared spectra. In this region, peaks appear at 1008, 1084 and 1112 cm −1 , attributed to basanite, although the last peak could also be attributed to 2–pyrrolidone [ 33 ]. Weak changes can be observed with temperature for both treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The band evolution in Region 2 ( Figure 6 b,d) is more complicated to describe because these peaks are very weak in the infrared spectra. In this region, peaks appear at 1008, 1084 and 1112 cm −1 , attributed to basanite, although the last peak could also be attributed to 2–pyrrolidone [ 33 ]. Weak changes can be observed with temperature for both treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The raw material used was calcium-sulphate hemihydrate (CaSO 4 ·½H 2 O) with a solution of 2–pyrrolidone binder with a high water content. The composition of the two raw materials was studied in previous work using different analytical techniques [ 33 ]. The results using Raman spectrometry and X-ray diffraction show that the powder has all the species of the system CaSO 4 ·H 2 O: gypsum, hemihydrate and anhydrite, with hemihydrate in its beta phase as the majority species.…”
Section: Methodsmentioning
confidence: 99%
“…The material used to print the binder jetting mold was a commercial powder plaster, CaSO 4 .1/2H 2 O (VisiJet PXL Core, from 3DSystems, Rock Hill, SC, USA) with a purity of 80-90%, according to the manufacturer and a commercial binder solution (VisiJet PXL Clear) based on water with 2% Pyrrolidone. The characterization of the powder and the binder were carried out by the authors in a previous work [32]. The mold was manufactured using binder jetting technology with a Project CJP 660Pro machine (3D Systems, Rock Hill, SC, USA).…”
Section: Materials and Molds Manufacturingmentioning
confidence: 99%
“…The powder is made up of a mixture of calcium sulfate, dehydrate, hemihydrate and anhydrous phases. In addition, it has some impurities or additives such as aluminium, sodium, magnesium, potassium, silicon [33]. The distribution of powder particles is D90 = 70.12 µm and the bulk particle density is 0.912 g/cm 3 [44].…”
Section: Binder Jetting Manufactured Mouldsmentioning
confidence: 99%
“…Binders such as furan are predominantly used in foundry applications, but they generate toxic and carcinogenic gases, harmful to operators and the environment. These aspects lead to important limitations, therefore it is necessary to investigate alternative materials for safer and environmentally friendly casting [33]. Rodriguez et al [34] demonstrated that the manufacture of moulds using the BJ technique with alternative materials can be an option for the use of furan resins.…”
Section: Introductionmentioning
confidence: 99%